2017
DOI: 10.1111/anu.12533
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of the defatted microalgae Nannochloropsis sp. and Desmodesmus sp. when fed to Atlantic salmon, Salmo salar

Abstract: The aim of the study was to investigate the apparent digestibility coefficient (ADC) of defatted biomass derived from microalgae Nannochloropsis sp. and Desmodesmus sp. when fed to Atlantic salmon postsmolts in seawater. Two experiments, one employing cold-pelleted and the other employing extruded pellets, were carried out to determine the ADC of dry matter (DM), protein, ash and energy. The test feeds consisted of a fishmeal-based reference feed and the algal biomass, at a ratio of 70:30, and yttrium oxide as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 64 publications
3
49
0
1
Order By: Relevance
“…was consistent with protein digestibility (72%) of Nannochloropsis sp. co-product (left-over algal meal from commercially grown algal biomass after extraction of oils for nutraceutical, chemical, or fuel applications) fed to Atlantic salmon (Gong et al, 2018). The values were, however, slightly lower than those for protein (81.1%) and essential amino acids (67-88%) of whole cells of Nannochloropsis sp.…”
Section: Digestibility Differences Between Isochrysis Sp and Nannochmentioning
confidence: 93%
See 1 more Smart Citation
“…was consistent with protein digestibility (72%) of Nannochloropsis sp. co-product (left-over algal meal from commercially grown algal biomass after extraction of oils for nutraceutical, chemical, or fuel applications) fed to Atlantic salmon (Gong et al, 2018). The values were, however, slightly lower than those for protein (81.1%) and essential amino acids (67-88%) of whole cells of Nannochloropsis sp.…”
Section: Digestibility Differences Between Isochrysis Sp and Nannochmentioning
confidence: 93%
“…Recent industrial-scale production of microalgae for biofuels and human nutritional supplements has stimulated interest in their use in animal feeds (Gouveia et al, 2009;Hemaiswarya et al, 2011;Ryckebosch et al, 2012) and especially for aquafeeds (Beal et al, 2018;Shah et al, 2018). Marine microalgae show promise as potential replacements for fishmeal and fish oil in feeds for salmonids and other finfish because of their elevated fatty acid profiles and high protein content (Walker and Berlinsky, 2011;Tibaldi et al, 2015;Kiron et al, 2016;Sarker et al, 2016aSarker et al, , 2016bGong et al, 2018;Sørensen et al, 2017;Bélanger-Lamonde et al, 2018). Our recent studies showed that whole cell biomass of Schizochytrium sp.…”
Section: Research Articlementioning
confidence: 99%
“…This composition would make this fraction very attractive as animal feed. However, true nutritional value, digestibility, palatability and potential toxicity should be experimentally determined (Gong et al, 2018). Although obtained in a quantitative smaller amount, yeast biomass would indeed represent a wanted animal feed ingredient (Øverland and Skrede, 2017).…”
Section: Biochemical Composition Of the Residual Biomassmentioning
confidence: 99%
“…As a result, there is a renewed interest in the use of novel feed resources for aquafeed. Microalgae, one of the novel feed ingredients, have been studied during the larvae stages (Eryalçın, Ganuza, Atalah, & Cruz, ; Rocha, Ribeiro, Costa, & Dinis, ) and during the grow‐out phases of fish (Gong, Guterres, Huntley, Sørensen, & Kiron, ; Sarker, Gamble, Kelson, & Kapuscinski, ; Teuling, Schrama, Gruppen, & Wierenga, ). In digestion trials for fish, microalgae are often fed in intact forms (Nandeesha, Gangadhara, Manissery, & Venkataraman, ; Sørensen, Berge, Reitan, & Ruyter, ; Teuling et al, ; Tibaldi et al, ).…”
Section: Introductionmentioning
confidence: 99%